2018
DOI: 10.5603/kp.a2018.0033
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D studies in cardiovascular diseases in eight Central and Eastern European countries: a systematic review of the literature

Abstract: The number of cardiovascular-related studies reporting HRQoL using EQ-5D has consistently increased in CEE countries over the past decade and is outstanding compared with other clinical fields. The EQ-5D index and EQ VAS scores varied based on the disease severity, patient characteristics, and treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…A study on QOL in patients with heart failure has confirmed the effectiveness of the EQ-5D (Boczor et al, 2019). Additionally, one literature review has shown that the number of cardiovascular-related studies reporting QOL using EQ-5D have consistently increased in many countries over the past decade, and its use is outstanding compared with other clinical fields (Batóg et al, 2018). The Cronbach alpha in this study for this assessment was 0.788.…”
Section: Methodssupporting
confidence: 61%
“…A study on QOL in patients with heart failure has confirmed the effectiveness of the EQ-5D (Boczor et al, 2019). Additionally, one literature review has shown that the number of cardiovascular-related studies reporting QOL using EQ-5D have consistently increased in many countries over the past decade, and its use is outstanding compared with other clinical fields (Batóg et al, 2018). The Cronbach alpha in this study for this assessment was 0.788.…”
Section: Methodssupporting
confidence: 61%
“…In the past 2 decades, the 3L has been administered to over 25 000 people in nearly 50 clinical and population studies in Hungary. 8,[48][49][50] Being aware of the substantial collection of Hungarian studies, we believe that a revision of the translation before this valuation study would have caused more harm than good.…”
Section: Discussionmentioning
confidence: 99%
“…The EQ-5D is, apart from the Short Form-36 (SF-36), one of the most popular generic instruments for the measurement of health-related quality of life (HRQoL) [1][2][3]. The questionnaire is available in two versions: original, three-level (EQ-5D-3L) and the more recent five-level form (EQ-5D-5L).…”
Section: Introductionmentioning
confidence: 99%